Role of NFAT in Chronic Lymphocytic Leukemia and Other B-Cell Malignancies - Sana, Ilenia; Mantione, Maria Elena; Angelillo, Piera; Muzio, Marta (Frontiers in Oncology, 2021)
In recent years significant progress has been made in the clinical management of chronic lymphocytic leukemia (CLL) as well as other B-cell malignancies; targeting proximal B-cell receptor signaling molecules such as Bruton Tyrosine Kinase (BTK) and Phosphoinositide 3-kinase (PI3Kδ) has emerged as a successful treatment strategy. Unfortunately, a proportion of patients are still not cured with available therapeutic options, thus efforts devoted to studying and identifying new potential druggable targets are warranted. B-cell receptor stimulation triggers a complex cascade of signaling events that eventually drives the activation of downstream transcription factors including Nuclear Factor of Activated T cells (NFAT). In this review, we summarize the literature on the expression and function of NFAT family members in CLL where NFAT is not only overexpressed but also constitutively activated; NFAT controls B-cell anergy and targeting this molecule using specific inhibitors impacts on CLL cell viability. Next, we extend our analysis on other mature B-cell lymphomas where a distinct pattern of expression and activation of NFAT is reported. We discuss the therapeutic potential of strategies aimed at targeting NFAT in B-cell malignancies not overlooking the fact that NFAT may play additional roles regulating the inflammatory microenvironment.